Evaluation of Proteolytic and Chitinolytic Activities of Indigenous Bacillus Species from Crab Shell Waste - Dliyauddin, Moh; Ardyati, Tri; Suharjono, Suharjono (The Journal of Experimental Life Science, 2020)
The increase of crab meat export activities in Indonesia leads to the accumulation of crab shell waste in a massive amount that can naturally degrade and causing bad odor. Naturally, microorganisms will degrade this waste through fermentation and enzymatic reaction, including protease and chitinase due to its high content of chitin and protein. Bacillus is the most potential bacteria to degrade crab shell waste, and indigenous Bacillus from this waste can increase the degradation rates. The aims of this study were to evaluate the proteolytic and chitinolytic activities of indigenous Bacillus species from crab shell waste. Bacillus cereus BP14 and Bacillus licheniformis CK20 as the chitinolytic bacteria, and Bacillus subtilis AP9 and Bacillus licheniformis AP5 as the proteolytic bacteria were isolated from crab shell waste and identified based on the 16S rDNA sequences. The bacterial isolates were grown in skim milk broth for proteolytic characterization and colloidal chitin broth for chitinolytic characterization. The growth rates of each bacteria were determined through the growth curves. The enzymatic activities were determined based on the international standard for protease and chitinase enzyme activities together with growth curve sampling to determine the best incubation time for obtaining the highest enzymatic activities. From the shortest to the longest generation times of the Bacillus species obtained were B. subtilis AP9, B. licheniformis CK20, B. cereus BP14, and B. licheniformis AP5, respectively. The best incubation time for producing the highest enzymatic activity varied among species. However, the end of the logarithmic phase was similar. All of the Bacillus species obtained from this study exhibited chitinolytic and proteolytic activity. Therefore, it can be used as promising candidates of biodegradation agents inenhancing the degradation rates of crab shell wastes.